(untitled) (Journal of Business Management and Accounting, 2016)
Social enterprise encounter has received enormous pressure to manage both social and economic objectives. This has given rise to tension in managing social and economic objectives leading to tension within the organisation. Failure to manage this tension and competing demands between these two objectives raise concerns toward mission drift issue. The paper discusses the conceptualisation of social enterprise and its competing demands, and the analysis of normative and empirical research on performance measurement system (PMS) and management control in social enterprise. From the normative literature, a number PMS models for social enterprise were advanced. However, there is lack of empirical research on management control and performance measurement in social enterprise, especially regarding the ways an organisation designs and uses its PMS to achieve a balance between social and economic objectives. Hence, a qualitative method is recommended as a developing strategy for managing the competing demands since they are very much dependent on the manner organisational view and deal with the needs of the two objectives.